Stress of conscience of COVID-19 among perianaesthesia nurses having worked in a COVID-ICU during the coronavirus pandemic: an international perspective - Ulrica Nilsson; Jan Odom-Forren; Mette Ring; Hanneke van Kooten; Joni M. Brady (BMC, 2022)
Abstract Background Several studies have reported that working in a COVID-ICU impacted nurses' mental well-being. Yet little is known about how perianaesthesia nurses who have been working in a COVID-ICU perceived their stress of conscience. The aim of this study was to: (1) describe and compare stress related to troubled conscience among perianaesthesia nurses in three countries who have been working in a COVID-ICU during the pandemic, (2) compare their levels of troubled conscience between working in a COVID-ICU and their usual workplace, and (3) compare nurses that usually work in an ICU department with nurses who usually work outside of the ICU. Methods A descriptive, international cross‐sectional online survey including the Stress of Conscience Questionnaire (SCQ) was distributed between organizational member countries of the International Collaboration of PeriAnaesthesia Nurses. Results A total of 246 nurses from three countries participated. Significant differences were found in stress of conscience when working in the Covid-ICU between Sweden 31.8 (8.6), Denmark 23.1 (8.6), and Netherlands 16.4 (6.5) p < 0.001. Significant differences were also found between nurses working in a COVID-ICU in contrast with their usual workplace: 23.1(5.6) versus 17.7(5.3), p < 0.001. The most stressful aspect of conscience reported was that work in the COVID-ICU was so demanding, nurses did not have sufficient energy to be involved with their family as much as they desired. No statistical differences were found between nurses that usually work in an ICU department with nurses who usually work outside of the ICU. Conclusion The COVID-19 pandemic has negatively impacted stress of conscience among nurses working in the COVID-ICU. Swedish nurses were found to be more significantly impacted. This could be related to low numbers of existing ICU beds and ICU nurses prior to the pandemic necessitating a longer time required for working in a COVID-ICU. Stress of conscience also increased when working in the Covid-ICU compared to working in the usual workplace, and the most stressing aspect reported was that COVID-ICU work was so demanding that nurses did not have the energy to devote themselves to their family as they would have liked.